The Connection Between the Shinjang Oirat Magical Tale “The boy took wife from a wolf” and the Wolf totem - D, Uranchimeg (Studia Folclorica, 2024)
The Oirat magical tale “The boy took a wife from wolf” from Shinjang has evolved from the mythic motif of a human marrying a non-human being and has merged with other folktale motifs, becoming a composite tale. In tracing its origins and developmental process, the study first conducts a detailed analysis of motifs from myths that explain the origins of Mongolic and Turkic-speaking ethnic groups. Then, a structural analysis of different versions of “The boy took a wife from wolf” within Shinjang Oirat magical tales is conducted. The findings illustrate that while the original motif of a human marrying a non-human being remained central, over time the tale lost its mythological essence and transformed into an ordinary folktale. Шинжааны “Чоноос эхнэр авсан хөвүүн” гэх шидэт үлгэр чоно тотемтой холбогдох нь Хураангуй: Шинжааны өөлдийн шидэт үлгэр дэх “Чоноос эхнэр авсан хөвүүн” гэдэг үлгэр нь хүн хийгээд ондоо төрөлтөн урагласан домгийн мотивоо улиран хөгжиж, бусад үлгэрийн мотивтой нийлж нийлмэл үлгэр болсон байна. Үүний үндэс сурвалж ба улирсан явцыг хайн сүвэгчлэхэд юуны урьд монгол, түрэг хэлтний овог угсаатны үүсэл гарлыг тайлбарласан домгуудын мотивоос гардан шинжилнэ. Дараа нь Шинжааны өөлдийн шидэт үлгэр дэх “Чоноос эхнэр авсан хөвүүн” гэдэг үлгэрийн хувилбаруудад хэв шинжийн задлан шинжилгээ хийж хүн ондоо төрөлтөнтэй урагласан домгийн мотив нь гол байснаа үргэлжилж угийн онцлогоо алдан явган үлгэрийн шинжтэй болсныг харуулна. Түлхүүр үг: шидэт үлгэр, хэв шинж, домгийн мотив, онцлог, явган үлгэр, чоноос эхнэр авах, хувилбар